Exploring Teachers' Perceptions of AI-Generated English Lesson Plans for Students with Intellectual Disabilities - Thaworn Worabuttara; phalaguna, ida bagus; Khwanjai Kaewsaeng (UHN IGB Sugriwa Denpasar, 2024)
This research explores teachers' perceptions of AI-generated English lesson plans specifically designed for students with intellectual disabilities. The objective is to assess the effectiveness and usability of AI tools, namely ChatGPT, in enhancing lesson planning for this unique student population. A mixed-methods approach was employed, combining qualitative interviews and quantitative surveys with 14 teachers who work with students with intellectual disabilities. The findings reveal a general satisfaction among teachers regarding the innovative ideas and time-saving benefits of AI-generated lesson plans. However, challenges were identified, including the inability of the AI to create multimedia content, discrepancies in formatting with government standards, and a lack of specificity in assessments. These insights highlight the potential of AI tools to support teachers while also underscoring the need for professional development and training to address the limitations encountered. The study concludes that while AI-generated lesson plans can enhance teaching practices, further research and support are essential to optimize their integration in special education settings.